Allocative Efficiency Measurement Revisited: Do We Really Need Input Prices? - Oleg Badunenko; Michael Fritsch; Andreas Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
The traditional approach to measuring allocative efficiency is based on input prices, which are rarely known at the firm level. This paper proposes a new approach to measure allocative efficiency which is based on the output-oriented distance to the frontier in a profit – technical efficiency space – and which does not require information on input prices. To validate the new approach, we perform a Monte-Carlo experiment which provides evidence that the estimates of the new and the traditional approach are highly correlated. Finally, as an illustration, we apply the new approach to a sample of about 900 enterprises from the chemical industry in Germany. – – ?Ein neuer Ansatz zur Messung allokativer Effizienz ? Sind Input-Preise wirklich erforderlich?? Der traditionelle Ansatz zur Messung allokativer Effizienz erfordert Informationen über Input-Preise der Unternehmen, die allerdings nur selten vorliegen. In diesem Aufsatz schlagen wir eine neue Methode zur Bestimmung der allokativen Effizienz vor, der als wesentliche Information den Abstand eines Unternehmens von der Effizienz-Grenze nutzt und keine Information über Input-Preise erfordert. Ein Monte-Carlo Experiment zur Überprüfung der Tragfähigkeit dieses Ansatzes zeigt, dass die Schätzwerte nach der traditionellen Methode und dem von uns vorgeschlagenen Verfahren eng miteinander korreliert sind. Zur Illustration wenden wir den neuen Ansatz auf ein Sample von 900 Unternehmen der Chemischen Industrie in Deutschland an.
Keywords: L65; D61; L25; L23; 330; Allokative Effizienz; Data Envelopment Analysis; Frontier Analysis; Technische Effizienz; Monte-Carlo Methode; Chemische Industrie; Allocative efficiency; data envelopment analysis; frontier analysis; technical efficiency; Monte-Carlo study; chemical industry